Evaluation of Tumor Necrosis Factor α (TNF-α) in Gingival Crevicular Fluid and Serum Before and After Phase I Therapy with Subgingival delivery of Hyaluronic Acid in Chronic Periodontitis Patients - Khalid Shaban; Atef alasfar; Nada Shaban (Khalij-Libya Journal of Dental and Medical Research, 2025)
The aim of this study was to estimate the levels of TNF-α in serum and gingival crevicular fluid, in patients with chronic periodontitis (CP), before and after phase I therapy with subgingival delivery of Hyaluronic acid (Gengigel Gel). A total of thirty subjects were included in this study; 20 CP patients as a study group (group I) and 10 systemically healthy subjects with clinically healthy gingiva as a control group (group II). The nonsurgical periodontal therapy (SRP) + HA gel were done in group I. Periodontal parameters, including PI, GI, BOP, PD and the CAL, were recorded. GCF and serum were collected from all individuals included in the study; the first sample was collected from all groups (study and control) before treatment. The second sample was collected 4 weeks after subgingival delivery of Hyaluronic acid & phase I therapy from group I. Levels of TNF-α in GCF and serum were quantified using ELISA. The results showed a statistically significant reduction in total levels of TNF-α in serum and TNF-α in GCF in study group after application of Hyaluronic acid with phase I therapy. Results also showed all clinical parameters were significantly improved after application of Hyaluronic acid with phase I therapy in groups I (p<0.001). Scaling and root planing (SRP) is the mainstay of treatment of periodontal diseases, furthermore subgingival application of Hyaluronic acid gel with SRP were effective in improving clinical parameters in CP patients. TNF-α level in serum and GCF are reduced after phase I therapy with application of Hyaluronic acid. الغرض من هذه الدراسة هو تقييم معدل عامل نخر الورم الفا في المصل والسائل اللثوي قبل وبعد العلاج الغير جراحي مع استخدام حامض الهيالورونيك كدواء موضعي في الجيوب اللتوية لمرضي التهاب الأنسجة الداعمة المزمن. اشتملت هذه الدراسة على تلاثون شخصا تم تقسيمهم الي مجموعتين: المجموعة الاولى احتوت على 20 مريض يعانون من التهاب اللأنسجة الداعمة للأسنان كمجموعة اختبار, والمجموعة الثانية احتوت على 10 اشخاص أصحاء لايعانون من أمراض اللثة كمجموعة ضابطة. وقد روعي عند اختيار الحالات ان يكونوا ضمن المعدل الطبيعي للوزن كما تمت مراعاة خلوهم من الامراض الجهازية و تم استبعاد المدخنين و الحوامل. تم تقيم كلا من عمق الجيوب اللثوية و معدل فقدان التلاصق بين اللثة والاسنان, و معامل اللثة ومعامل تراكم البلاك ومعامل الادماء اللثوي قبل البدء في العلاج وبعد الانتهاء منه. وتم جمع السائل اللثوي و المصل من جميع الأفراد الواردة في الدراسة. وقد تم جمع العينة الأولى من المجموعتين (دراسة و ضابطة) قبل كحت وازالة الرواسب الجيرية وتنعيم اسطح الجذور ,واستخدام حامض الهيالورونيك في الجيوب اللتوية. العينة الثانية جمعت بعد 4 أسابيع من كحت وازالة الرواسب الجيرية، وتنعيم اسطح الجذور وتطبيق حامض الهيالورونيك في الجيوب اللتوية للمجموعة الاولي فقط. يتم قياس تركيزعامل نخر الورم الفا في السائل اللثوي و المصل كميا باستخدام ELISA كما تم اجراء التحليلات البيانية باستخدام البرنامج الاحصائي SPSS. واظهرت نتائج الدراسة الحالية أن هناك تحسن سريري وفروق ذات دلالة إحصائية فى قياس جميع المظاهر السريرية بعد العلاج اللثوي لمجموعةالاختبار باستخدام حامض الهيالورونيك في الجيوب اللتوية. وكدلك اظهرت الدراسة انخفاض في معدلات عامل نخر الورم الفا في المصل و السائل اللثوي بعد العلاج الغير جراحي و استخدام حامض الهيالورونيك في الجيوب اللتوية في مجموعة الاختبار. تدعم هذه الدراسة ان استخدام الادوية الموضعية بالاضافة الي كحت وازالة الرواسب الجيرية, وتنعيم أسطح الجذور لمجموعة الاختبارهي الطريقة الفعالة لعلاج الامراض اللثوية وقد حققت تحسنات سريرية وفروق ذات دلالة احصائية في قياس جميع المظاهر السريرية. تشير الدراسة أيضا إلى أن تقييم مستويات عامل نخر الورم الفا في مصل الدم و السائل اللثوي قد يكون مفيد لمراقبة نشاط الالتهابات اللثوية والاستجابة للعلاجات الغير الجراحية بمساعدة الادوية الموضعية كما ينصح باجراء المزيد من الدراسات علي عدد اكبر من الحالات واستخدام طرق علاجية مختلفة